STRATEGIC NETWORK PLANNING FOR OPTIMIZING DIGITAL TRANSFORMATION IN THE COAL MINING INDUSTRY - Pratama, Rizqi; S, Angga Margi; Farzan, Arisal (Ridwan Institute, 2024)
The coal mining industry is one of the most important sectors in Indonesia's economy, and it has become a vital part of the national economy. As a result, the mining industry has become more and more digital. The application of the overlay method in this study aims to improve operational efficiency and work safety in the coal mine of PT Putra Perkasa Abadi (PPA) in Indonesia. The overlay method combines WiFi and LTE networks in the mining area, which improves network performance in terms of throughput, latency, packet loss, and signal coverage. The implementation of Strategic Network Planning to Optimize Digital Transformation in the Coal Mining Industry has proven to be effective in improving the quality of networks that support digital transformation in mining areas. The solution has the potential to be applied to other industrial sectors with similar operational challenges, optimizing the use of network technologies to support sustainability and productivity. Overall, this study makes a significant contribution to designing and implementing network systems that can support operational efficiency, improve occupational safety, and offer sustainable and adaptive solutions in the industry, ultimately supporting the digitalization and transformation of the industry.